181 Associated factors to the presence of serious infections in a large cohort of juvenile-onset systemic lupus erythematosus. (April 2019) - Maria Pego Reigosa, Jose; Torrente-Segarra, Vicenç; Perez, Victor Del Campo; Salman-Monte, Tarek; Narváez-García, Javier; López-Longo, Francisco Javier; Ovalles, Juan; Rubio, Paula; Izquierdo, Maria Galindo; Andréu-Sánchez, José L; Alen, Jaime Calvo; Uriarte, Esther; et al.
Abstract : Background: Serious infections are included as one of the main causes of mortality in juvenile-onset systemic lupus erythematosus (jSLE) patients (Torrente-Segarra et al1) and a predictor of poor prognosis in SLE. We aimed to assess the incidence of serious infection and investigate the associated factors and clinical impact in a large jSLE retrospective cohort. Methods: All patients in the Spanish Rheumatology Society Lupus Registry (RELESSER) who meet 4 ACR-97 SLE criteria with disease onset before the age of 18 (jSLE) (Rúa-Figueroa et al2), were retrospectively investigated for serious infections (defined as either the need for hospitalization with parenteral antibiotherapy for a potentially fatal infection or death caused by the infection). Patients with and without infections were compared in terms of jSLE severity, damage, comorbidities, and demographic characteristics. A multivariable Cox regression model was built to calculate hazard ratios (HRs) for the first infection. Results: A total of 353 jSLE patients were included: 88.7% female, median age at diagnosis: 14.3 years (SD 2.9), and mean disease duration: 16.0 years (SD 9.3). A total of 104 (29.5%) patients suffered 1 serious infection (1: 55.8%; 2–5: 38.4%, and 6 infections: 5.8%). Sociodemographic data is shown in table 1. Total serious infections recorded in these patients numbered 205. The incidence rate was 3.7 (95%CI: 3.24.2) infections per 100 patient years. In the bivariate analysis we found association between serious infections and smoking (p=0.018), lupus nephritis (p<0.001), kidney transplantation (p=0.017), corticosteroids use (p=0.02), higher corticosteroids dosage (p<0.001), immunosupressants use (p<0.001)- azathioprine, mycophenolate, cychlophosphamide and rituximab, hospitalization due to jSLE flare (p<0.001), higher SLEDAI score (p=0.026), higher KATZ score (p<0.001) and higher CHARLSON score(p=0.02). Serious infection localization and causal agent are described in table 1, being respiratory and bacterial infections the most frequent, respectively. In the logistic regression analysis the use of cyclophosphamide, mycophenolate and rituximab and SLICC score showed association to serious infection (OR 2, 55 [1, 44–4, 52], OR 1, 4 [1, 17–1, 66], respectively; p<0.001). In the Cox regression analysis, the following were all associated with serious infection (p<0.01): splenectomy, use of cyclophosphamide, mycophenolate and rituximab, which is shown in figure 1 and figure 2. Conclusions: In the largest observational European Registry of SLE patients, one third of the jSLE patients suffered serious infections. Higher SLEDAI score, renal involvement and immunosupressant and corticosteroids use were independent associated factors to the presence of serious infection in jSLE, as well as smoking. Funding Source(s): FIS Grant PI11/02857 (Instituto Carlos III, Fondos FEDER) has supported this work.